(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
The paper offers an analysis of the Italian Constitutional Court’s judgement that declared the Friuli Venezia Giulia regional law on living wills unconstitutional. The regional law provided for the institution of a registry for living wills within the regional health system. By regulating the administrative procedures at the regional level, the region intervened on aspects pertaining to the state legislative competence in civil and criminal law, since it laid down the guidelines for the drafting of living wills and of their contents and for the definition of their legal enforceability. As these are issues which are strictly connected with individual fundamental rights, regulating exclusively practical aspects without interfering with the subject-matter entrusted to the administration may prove to be difficult.